3D printed bio-models for medical applications - Yap, Yee Ling (2020)
Purpose - The design process of a bio-model involves multiple factors including data acquisition technique, material requirement, resolution of the printing technique,cost effectiveness of the printing process and end use requirements.This paper aims to compare and highlight the effects of these design factors on the printing outcome of bio-models. Design/methodology/approach - Different data sources including engineering drawing, computed tomography (CT), and optical coherence tomography (OCT) were converted to a printable data format. Three different bio-models, namely, an ophthalmic model, a retina model and a distal tibia model, were printed using two different techniques, namely, PolyJet and fused deposition modelling. The process ﬂow and 3D printed models were analysed. Findings - The data acquisition and 3D printing process affect the overall printing resolution. The design process ﬂows using different data sources were established and the bio-models were printed successfully. Research limitations/implications - Data acquisition techniques contained inherent noise data and resulted in inaccuracies during data conversion. Originality/value - This work showed that the data acquisition and conversion technique had a signiﬁcant effect on the quality of the bio-model blueprint and subsequently the printing outcome. In addition, important design factors of bio-models were highlighted such as material requirement and the cost-effectiveness of the printing technique. This paper provides a systematic discussion for future development of an engineering design process in three-dimensional (3D) printed bio-models.